Assessment of prescribing pattern based on WHO indicators at “X” Primary Health Care in Sleman Regency - Kristy Tri Wardhani; Dian Medisa; Saepudin Saepudin; Ifada Ifada (Universitas Islam Indonesia, 2022)
Abstract Background: Puskesmas is a primary level of health service facility that must implement rational drug use. A rational prescribing pattern will improve the quality of health services.Objective: The aim of this study was to know the prescribing pattern at the